Blending Ratio of Recycled Aggregate on the Performance of Pervious Concrete (Fracture and Structural Integrity, 2018)
Recycled pervious concrete as an environment-friendly and material-saving construction material can satisfy the current development demands of circular economy and environmental protection in China. But studies concerning the performance of recycled pervious concrete are not enough, which limits its application and promotion. In this study, waste prefabricated concrete beams were taken as the source of recycled aggregate and processed by crushing and screening to obtain recycled coarse aggregate. Then pervious concrete was prepared using the recycled coarse aggregate. Taking replacement rate and grain size grade as the running parameters, five groups of mix proportion were designed. Moreover the physical, mechanical and permeability performance and the interrelation were analyzed by tests. The results demonstrated that the 24-hour water absorption rate of the recycled coarse aggregate was 12 times higher than that of natural aggregate, the porosity of the pervious concrete was between 14.2% and 20.44%, and the permeability coefficient was between 0.19 cm and 0.46 cm and increased with the increase of the porosity. The compressive strength of the pervious concrete increased with the increase of the replacement rate. When the replacement rate was 30%, the improvement amplitude was the largest. The compressive strength was improved 35.4% after double grain grade aggregate was mixed, but the permeability performance decreased.
Keywords: Recycled aggregate; Pervious concrete; Permeability; Strength